A Development of the Economic Theory of Price Index Numbers - Staehle, H. (Review of Economic Studies, 1935)
Journal Article A Development of the Economic Theory of Price Index Numbers Get access H. Staehle H. Staehle Geneva Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 2, Issue 3, June 1935, Pages 163–188, https://doi.org/10.2307/2967585 Published: 01 June 1935